Patrulius Olistolith – A large jurassic limestone block in Albian Conglomerates of the Bucegi Mountains, Southeast Carpathians, Romania (Geo-Eco-Marina, 2019)
The paper introduces and describes the Patrulius Olistolith, one of the largest exotic blocks (218 m long, 110 m wide and 55 m thick) embedded in Albian conglomerates from the Carpathian Bend area (southern part of Eastern Carpathians, Romania). The Albian conglomerates embedding the Patrulius Olistolith are deposits with homogeneous internal structure and poor sorting, features typical of debris flow sediments. Based on this character, it is considered that the Patrulius Olistolith transport was a gravitational collapse process and that it was transported as a very large clast within the mass flow conglomerates.The olistolith-embedding conglomerates also have sedimentary features (small matrix amount, normal grading and some internal sedimentary structures) not typically produced by mass transport process, which points out the special nature of the transport and sedimentation processes responsible for the deposition of the conglomerates and embedded olistoliths, and calls for further sedimentological investigations. Like the other Albian Bucegi olistoliths, the Patrulius Olistolith was subjected to an estimated 10 km marine transfer, its transportation taking place in shallow waters.
Keywords: exotic blocks; mass transport; debris flow conglomerates; olistolith transport